(untitled) (Papeles, 2024)
The article examines a phenomenon observed in a thesis research regarding the research agendas at the Faculty of Philosophy, Humanities, and Arts of UNSJ. It specifically focuses on the gap between the themes addressed, fields of application, and the formats for disseminating knowledge from the research projects. The analysis is based on the disciplinary areas of the analyzed projects to identify differential strategies in the choice of formats for knowledge circulation produced within the institution. The research is structured in two analytical moments: one objective-structural and another subjective-ethnographic. Elements from both instances are considered to address the specific issue of the gap between research agendas and dissemination formats.